Analysis of Translation Methods Used in The Subtitle of The Netflix Series Wednesday (2022) - Fauziah, Jihan; Simatupang, Ervina CM (Universitas Cokroaminoto Palopo, 2024)
This study analyzes the translation methods used in the subtitle of the Netflix series Wednesday (2022) The series broke the record by reaching 400 million viewers in just a week. The author focuses on finding the factors that caused the subtitle to be translated. This study uses a qualitative textual analysis method. The author describes the data sample descriptively without using data in the form of numbers. Smith (2017) says this method involves examining and generating data from objects like newspaper, film, or blog posts. Based on the data analysis, the type of translation method found in the subtitle of the Netflix series Wednesday are communicative (38.00%), adaptation (34.00%), idiomatic (02.00%), and other translation method (26.00%) which communicative is the most used type of translation method and idiomatic is the least used type of translation method. In addition, based on the data analysis, the type of translation techniques applied in the subtitle are established equivalence (30.00%), calque (30.00%), and other techniques (38.00%). The most commonly used technique are calque and established equivalence, while particularization is the most least used (02.00%).